User-independent optical path length compensation scheme with sub-nanosecond timing resolution for a 1 x N quantum key distribution network system - Park, Byung Kwon; Woo, Min Ki; Kim, Yong-Su; Cho, Young-Wook; Moon, Sung; Han, Sang-Wook (OPTICAL SOC AMER, 2020)
Quantum key distribution (QKD) networks constitute promising solutions for secure communication. Beyond conventional point-to-point QKD, we developed 1 x N QKD network systems with a sub-nanosecond resolution optical path length compensation scheme. With a practical plug-and-play QKD architecture and compact timing control modules based on a field-programmable gate array, we achieved long-term stable operation of a 1 x 64 QKD network system. Using this architecture, 64 users can simultaneously share secret keys with one server, without using complex software algorithms and expensive hardware. We demonstrated the workings of a 1 x 4 QKD network system using the fiber network of a metropolitan area. (C) 2020 Chinese Laser Press
Keywords: FIELD-TEST; CRYPTOGRAPHY; PLUG